Antimicrobial (AM) effects of strach-based film incorporated with lysozymes and lauric acid - Khairuddin, Nozieana (2005)
Antimicrobial (AM) film applying a bio-switch concept is an active packaging concept that is now being commercialized in food packaging industries. By that, an investigation to determine a suitable formulation for starch-based film is done that consists of corn flour, tapioca flour, pure starch and soluble starch. Pure starch has the best film output which is translucent and elastic. AM compounds i.e. Lauric acid and Lysozyme were incorporated into formed film at different concentration. Incorporation of AM compound affects the appearance and texture of the film. Luria agar was prepared to culture Escherichia coli for inhibition test. The inhibition of E.coli from the AM film was observed in the broth and culture agar test. The inhibition effect increased with the increase in AM concentrations. Lysozymes-incorporated films show better inhibition than Lauric acid-incorporated films in both tests.